Dual role of boron-doped diamond (BDD) anode in effluent organic matter degradation and ultrafiltration membrane fouling mitigation. (February 2022) - Zeng, Weichen; Bai, Langming; Liang, Heng; Li, Guibai; Zhang, Han; Wang, Jinlong; Gan, Zhendong; Lin, Dachao; Guo, Yuanqing; Shao, Penghui
Abstract: Ultrafiltration (UF) is effective in retaining macromolecules during tertiary treatment, but the membrane fouling caused by the effluent organic matter (EfOM) limits its application. This study employed electrochemical oxidation (EO) as a pretreatment method for UF in tertiary treatment to investigate the effects of anode materials on membrane fouling alleviation and EfOM degradation. Compared with the dimensionally stable (DSA) and platinum (Pt) anodes, EO with a boron-doped diamond (BDD) anode exhibited better performances for membrane fouling mitigation due to the higher hydroxyl radical production activity of the BDD anode. It was observed that the current density and electrolysis time were closely related to membrane fouling when using a BDD anode, where increasing the current density or electrolysis time led to a significant improvement of specific flux. The BDD-based pre-oxidation efficiently removed 64% DOC, 76% UV254, and 95% fluorescence organic matter in EfOM, among which the concentrations of DOC and UV2 54 were positively correlated with the total fouling index (TFI). Meanwhile, 70% SMX in the secondary effluent was removed by the BDD anode. Furthermore, the BDD anode also mitigated membrane fouling by decomposing high molecular weight organic matter into smaller fractions and enhancing the electrostatic repulsion between membrane and EfOM. Therefore, the BDD-based EO process is a promising pretreatment strategy for UF to alleviate membrane fouling and improve the permeate quality. Graphical abstract: Image 1 Highlights: The BDD anode effectively alleviated membrane fouling caused by EfOM. DOC and UV254 were positively correlated with membrane fouling. Mechanisms of membrane fouling for the hybrid process were proposed. EO integrated with UF remarkably enhanced the removal efficiency of SMX.